Cooperative Learning An Effective Teaching Learning Strategy for Mathematics - Fathima, Roohi (INDIAN EDUCATIONAL REVIEW, 2019)
Cooperative learning represents a shift in educational paradigm from teacher-centered approach to student-centered learning in small groups. It is a strategy in which the learning takes place in small groups where students share ideas and work collaboratively to complete a given task. The present study attempted to learn the effect of cooperative system of learning on the achievement in mathematics of Class X students. Two sections of Class X, with 30 and 32 female students, respectively, were randomly selected to participate in the study over a period of three weeks. Both qualitative and quantitative methods were used that focussed on examining students’ participation while working on in-class cooperative learning activities in two different seating arrangements— rows and columns, and circles— as well as its impact on their achievement. Results show that cooperative learning helps to improve not only the understanding of the students but also motivate them to discuss the difficulties during the study, helped all students alike in terms of classroom participation and thereby improved their performance. The study underlines the fact that students should be encouraged to work in groups and to depend more on each other rather than the teacher to learn more efficiently.